Avoidance of sun exposure as a risk factor for major causes of death: a competing risk analysis of the Melanoma in Southern Sweden cohort. (16th March 2016) - Lindqvist, P. G.; Epstein, E.; Nielsen, K.; Landin‐Olsson, M.; Ingvar, C.; Olsson, H.
Abstract: Objective: Women with active sunlight exposure habits experience a lower mortality rate than women who avoid sun exposure; however, they are at an increased risk of skin cancer. We aimed to explore the differences in main causes of death according to sun exposure. Methods: We assessed the differences in sun exposure as a risk factor for all‐cause mortality in a competing risk scenario for 29 518 Swedish women in a prospective 20‐year follow‐up of the Melanoma in Southern Sweden (MISS) cohort. Women were recruited from 1990 to 1992 (aged 25–64 years at the start of the study). We obtained detailed information at baseline on sun exposure habits and potential confounders. The data were analysed using modern survival statistics. Results: Women with active sun exposure habits were mainly at a lower risk of cardiovascular disease (CVD) and noncancer/non‐CVD death as compared to those who avoided sun exposure. As a result of their increased survival, the relative contribution of cancer death increased in these women. Nonsmokers who avoided sun exposure had a life expectancy similar to smokers in the highest sun exposure group, indicating that avoidance of sun exposure is a risk factor for death of a similar magnitude as smoking. Compared to the highest sun exposure group, life expectancy of avoiders of sun exposure was reduced by 0.6–2.1 years. Conclusion: The longer life expectancy amongst women with active sun exposure habits was related to a decrease in CVD and noncancer/non‐CVD mortality, causing the relative contribution of death due to cancer to increase.